Experimental study on the hydro-thermal-deformation characteristics of cement-stabilized soil exposed to freeze–thaw cycles - Lu, Jianguo; Tan, Liling; Yang, Huohai; Wan, Xusheng; Wang, Yindong; Yan, Zhongrui (Frontiers in Earth Science, 2023)
It is significant to explore the hydro-thermal characteristics and deformation behaviors of cement-stabilized soils for the prevention and controlling of freeze-thaw damages in cold region engineering. In this study, six groups of cement-stabilized soil samples with different cement contents (i.e., 3%, 6%, 9%, 12%, 15%, and 18%) are be used to investigate the variations in soil temperature, volumetric unfrozen water content and deformation, as well freezing temperature and dry density. Results show that the temperatures of the cement-stabilized soil samples during the freezing and thawing processes can be categorized into three stages, and that the freezing temperature decreases with the cement content increased. Besides, the cement content and ambient temperature significantly affect the volumetric unfrozen water content of the cement-stabilized soil samples during the freeze-thaw cycles, and the soil temperatures corresponding to the peak value of hysteresis degree are relatively consistent with the freezing temperature. The residual volumetric unfrozen water content primarily depends on not only the cement content, but also the cement freezing condition. Although the variations of volumetric unfrozen water contents during the freezing and thawing processes are similar, the temperature change ranges differ significantly, particularly in the drastic phase transition zone. Additionally, adding cement into soils can effectively inhibit deformation, which is mainly due to the dual positive effects of the liquid water reduction owing to hydration reaction and structure compaction owing to the filling of hydration products.